2003
DOI: 10.1590/s0036-46652003000300009
|View full text |Cite
|
Sign up to set email alerts
|

Mycotic bovine nasal granuloma

Abstract: A case of mycotic bovine nasal granuloma in a 10 year-old Jersey cow, produced by Drechslera halodes is presented. Histopathological sections showed abundant hyaline and pigmented extra and intracellular fungal structures together with a polymorphic cellular granuloma formed by neutrophils, lymphocytes, plasmocytes, histiocytes and giant cells of the Langhans type. It is the first case of mycotic bovine nasal granuloma recognized in Uruguay although this disease seems to be frequent according to the opinion of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…rostratum exists widely in nature and can survive as a saprophyte in soil (Liu et al 2008), elephant dung (Jeamjitt et al 2006), as an endophyte in plants (Sappapan et al 2008), and can cause diseases in many plants (Zummo 1986;Leonard et al 1988;Okoli and Erinle 1990;Luan et al 2004;Cardona and González 2007), animals (Contidíaz et al 2003) and humans (Saint-Jean et al 2007), revealing a considerably broad range of genetic diversity in its population. Intraspecific variation of E. rostratum was also confirmed in Brn1 gene sequences (Zhang and Sun 2005).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…rostratum exists widely in nature and can survive as a saprophyte in soil (Liu et al 2008), elephant dung (Jeamjitt et al 2006), as an endophyte in plants (Sappapan et al 2008), and can cause diseases in many plants (Zummo 1986;Leonard et al 1988;Okoli and Erinle 1990;Luan et al 2004;Cardona and González 2007), animals (Contidíaz et al 2003) and humans (Saint-Jean et al 2007), revealing a considerably broad range of genetic diversity in its population. Intraspecific variation of E. rostratum was also confirmed in Brn1 gene sequences (Zhang and Sun 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Eight plant species have been reported as natural hosts of E. rostratum in China (Sun et al 1997;Tsai et al 2001;Luan et al 2004), while approximately another 20 plant species were confirmed to be hosts of E. rostratum through artificial inoculations (Chandramohan and Charudattan 2001;Tsai et al 2001). In addition, E. rostratum is known to cause diseases in both animals and humans (Contidíaz et al 2003;Saint-Jean et al 2007). To establish a science-based control strategy against the new banana leaf spot disease and evaluate the potential adverse effect of E. rostratum to banana plants, biological characterization of the pathogen is needed.…”
Section: Introductionmentioning
confidence: 99%
“…infection in cattle, including the presence of a Splendore-Hoeppli 9,13,16 reaction and hyphae within giant cells, macrophage, or free in tissues. 1,3,9,12,13,16 Eosinophils have also been observed in lesions associated with these fungi in cattle. 9,12,13,16 Although a few fungal elements were pigmented in the H&E sections that we examined, the use of unstained sections and FM stain were very useful in demonstrating pigment.…”
Section: Brief-report2023mentioning
confidence: 99%
“…causing mycotic bovine nasal granulomas have been reported, including cases caused by Drechslera sp. 1,12 and D. rostrata. 9 D. rostrata has also been reported as the cause of eumycotic mycetoma in a cow affecting the nasal cavity, skin, and lymph nodes.…”
Section: Brief-report2023mentioning
confidence: 99%
See 1 more Smart Citation